Microcredit, micro enterprising and repayment myth: The case of micro and small women business entrepreneurs in Tanzania - Tundui, Charles S.; Tundui, Hawa P. (World Scholars, 2024)
A research article submitted to the American Journal of Business and Management Vol. 2, No. 1, 2013, 20-30